2010
DOI: 10.1590/s0102-33062010000400017
|View full text |Cite
|
Sign up to set email alerts
|

Plantas nativas úteis na Vila dos Pescadores da Reserva Extrativista Marinha Caeté-Taperaçu, Pará, Brasil

Abstract: IntroduçãoO estudo da relação entre os indivíduos de determinada cultura e as plantas do seu meio, constitui o ramo da ciência chamado de etnobotânica (Albuquerque 2005). Estudos etnobotânicos tem trazido ao conhecimento do público e da comunidade científi ca o uso e a importância cultural, alimentar e medicinal das plantas para povos indígenas e comunidades tradicionais. Conhecendo e valorizando seus recursos naturais, populações nativas podem contribuir na manutenção da biodiversidade e dos recursos naturais… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 18 publications
0
17
0
8
Order By: Relevance
“…The climate is hot and humid, with a rainy season (from January to June) and a dry season (from July to December) [8][9]. The vegetation is composed of moderately preserved mangrove forest with species such as Rhizophora mangle, Avicennia germinans and Laguncularia racemosa [10](Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…The climate is hot and humid, with a rainy season (from January to June) and a dry season (from July to December) [8][9]. The vegetation is composed of moderately preserved mangrove forest with species such as Rhizophora mangle, Avicennia germinans and Laguncularia racemosa [10](Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…The overall reduction in average diameter across all three species and the lower average height and diameter nearer the creek suggest that trees with larger trunks are logged selectively in this area. Deus et al (2003) reported wood extraction from this mangrove area, and all three species are used for firewood and charcoal (Lacerda and Schaeffer-Novelli 1999;Marcelino et al 1999;Walters et al 2008;Carneiro et al 2010;Meireles 2016).…”
Section: Rhiz Manglementioning
confidence: 99%
“…Albertasse Almeida & Bandeira 2010;Althaus-Ottman et al 2010;Barroso & Hanazaki 2010;Carneiro et al 2010;Carniello et al 2010;Christo et al 2010;Costa & Mitja 2010;Giraldi & Hanazaki 2010;Merétika et al 2010;Oliveira et al 2010a;Oliveira et al 2010b;Oliveira et al 2010c;Roque et al 2010;Silva & Freire 2010;Zuchiwschi et al 2010;Brito & Senna-Valle 2011;Costa & Mayworm 2011;Cunha & Bortoloto 2011;Gandolfo & Hanazaki 2011;Lima et al 2011;Marinho et al 2011;Oliveira et al 2011;Mattos et al 2012;Miranda & Hanazaki et al 2011;Siviero et al 2011;Silva et al 2011;Aguiar & Barros 2012;Araújo & Amorozo 2012;Brito & Senna-Valle 2012;Castro et al 2012;Chaves & Barros 2012;Cunha-Lima et al 2012;Espinosa et al 2012;Freitas et al 2012;Gomes & Bandeira 2012;González-Perez et al 2012;Lima et al 2012;Lucena et al 2012;Nunes et al 2012;Oliveira & Menini-Neto 2012;Paulino et al 2012;Poderoso ...…”
Section: -2012 (47 Articles)mentioning
confidence: 99%